A framework for understanding poverty a cognitive approach - Payne, Ruby K. (Texas Process, Inc., 2005)
The 5th edition features an enhanced chapter on instruction and achievement; greater emphasis on the thinking, community, and learning patterns involved in breaking out of poverty; plentiful citations, new case studies, and data: more details findings about interventions, resources, and causes of poverty, and a review of the outlook for people in poverty---and those who work with them.
Includes bibliographical references (pages 207-230) and index.
Keywords: Poor--United States